Qualitative and Quantitative Research Findings: Literature Review in Educational Context - Oktariana Oktariana; Mohammad Muspawi (Universitas Muhammadiyah Enrekang, 2024)
This study aiming For analyze findings research that uses approach qualitative and quantitative in context education, with method study literature. Research This show that approach qualitative give outlook deep about interaction social and experience individuals in the environment education, while approach quantitative produce empirical data that can generalized. Combination from second approach This give better understanding​ comprehensive about factors that influence performance education, including role leadership transformational and cultural collaborative. Literature review This recommend use method study more mix​ wide For get comprehensive and in - depth results, as well push development leadership transformational in schools use increase results learning.